The seasonal characteristics of English Channel storminess have changed since the 19th Century - Richard C. Cornes; Philip D. Jones (Communications Earth & Environment, 2024)
Abstract Information from a variety of sources has suggested that increased storminess was experienced across the British Isles in the late eighteenth/early nineteenth century. However, it is not clear how stormy that period was relative to current conditions. Using newly recovered barometric pressure data that extend back to 1748 we have constructed a measure of geostrophic wind speed for the English Channel region using a pressure-triangle approach. We show that the 1790−1820s was a period of increased storminess across the region. This storminess extended throughout the year, which is different to comparable increases observed since the 1990s, which were confined to the winter season. While a strengthened North Atlantic jet stream is implicated in both periods, in the earlier period it is likely that the storm track shifted slightly to a more southerly location. We discuss the potential forcing mechanisms responsible for the changes in storminess over this multi-century timeframe.